Residents’ Attitudes and Perception towards Tourism Development: A Case Study of Rural Tourism in Dragacevo, Serbia - Blešić, Ivana; Pivac, Tatjana; Besermenji, Snežana; Ivkov-Džigurski, Andjelija; Košić, Kristina (Eastern European Countryside, 2024)
This research examined the residents’ profile, attitudes, and perception towards tourism development based on 176 respondents interviewed. Residents’ attitudes toward tourism were measured by adapting 24 items from the Tourism Impact Attitude Scale developed by Lankford and Howard (1994). This study aimed at identifying the relationships between residents’ socio-economic and demographic attributes and their attitudes toward tourism by focusing on villages where tourism is in the development stage.